REGRESSIVE MODEL OF SELF-REALIZATION PROCESS FACTORS FOR TECHNICAL UNIVERSITY INSTRUCTORS - Yakovytska, Lada (PSYCHOLOGICAL JOURNAL, 2017)
Studying the determinants of instructor’s self-realization in the sphere of science and technology, we get out of the fact that the system which is determinant is not some maximally extended complex of deterministic factors, but it is namely a well-structured and well-calculated system, all elements of which are in regular interconnection. Now, simulation is an effective technique to get knowledge about the nature of the studied phenomena. Linear regression analysis is the most common tool to describe the connection between some factors and some dependent value. Considerable calculating difficulties, which are associated with high dimension vast of initial signs, led to the fact that in the practice of designing psychodiagnostic models are used the simplest algorithms for determination of the linear regression model. The more severe the condition of selected feature independence is followed, the better the result is. The aim of the investigation is descriptive and comparative analysis of self-realization process factors for technical university instructors by calculation, and the construction of regressive models based on a preliminary study of the self-realization process for instructors of technical and economic departments, the emphasis of its essential characteristics. During the empirical research, the randomized sample have set 262 persons (engineers and instructors of technical departments) and 137 people (instructors of economic faculties). The previous research result analysis showed that there are differences in choices not only in terms of work experience in science and technology, but also on the direction of the department, that’s why models for instructors of technical and economic departments, considering the duration of professional standing, were separately counted. The designed models of self-realization process for technical university lecturers include both positive and negative factors, and may serve as a diagnostic tool for the analysis and successful development of specialist’s creativity.